Responsivity of porous silicon for blue visible light with high sensitivity - Ali, Iftikhar M. (Iraqi Journal of Physics, 2018)
In this work, porous silicon (PS) are fabricated using electrochemical etching (ECE) process for p-type crystalline silicon (c-Si) wafers of (100) orientation. The structural, morphological and electrical properties of PS synthesized at etching current density of (10, 20, 30) mA/cm2 at constant etching time 10 min are studied. From X-ray diffraction (XRD) measurement, the value of FWHM is in general decreases with increasing current density for p-type porous silicon (p-PS). Atomic force microscope (AFM) showed that for p-PS the average pore diameter decreases at 20 mA. Porous silicon which formed on silicon will be a junction so I-V characteristics have been studied in the dark to calculate ideality factor (n), and saturation current (Is) for these junctions. These junctions are used in photo sensors applications, where the photo sensors have been examined at blue light region. Sensitivity, rise and fall times have been calculated for this wavelength, the maximum value for sensitivity is (3797.6 %) at etching current density 10 mA/cm2 under blue light illumination at zero bias voltage.